Acceptability and use of a virtual support group for HIV-positive youth in Khayelitsha, Cape Town using the MXit social networking platform. Issue 7 (2nd July 2016) - Henwood, Ruth; Patten, Gabriela; Barnett, Whitney; Hwang, Bella; Metcalf, Carol; Hacking, Damian; Wilkinson, Lynne
ABSTRACT: Introduction : Médecins Sans Frontières supports human immunodeficiency virus (HIV)-infected youth, aged 12–25 years, at a clinic in Khayelitsha, South Africa. Patients are enrolled in youth clubs, and provided with a virtual chat room, using the cell-phone-based social networking platform, MXit, to support members between monthly/bimonthly club meetings. The acceptability and uptake of MXit was assessed. Methods : MXit was facilitated by lay counsellors, was password protected, and participants could enter and leave at will. Club members were asked to complete self-administered questionnaires and participate in two focus-group discussions. Results and discussion : In total, 60 club members completed the questionnaire, and 12 participated in the focus groups. Fifty-eight percentage were aged 23–25 years, 63% were female and 83% had a cell phone. Sixty percentage had used MXit before, with 38% having used it in the past month. Sixty-five percentage were aware of the chat-room and 39% knew how to access it. Thirty-four percentage used the chat-room at least once, 20% had visited the chat-room in the past month, and 29% had used MXit to have private conversations with other club members. Fifty-seven percentage used the chat-room to get advice, and 84% of all respondents felt that offering a service outside the youth club meetings was important and would like to see one to continue. The cost of using social media platforms was an issue with some, as well as the need for anonymity. Preference for other platforms, logistical obstacles, or loss of interest contributed to non-use. Conclusions : Reported usage of the MXit chat-room was low, but participants indicated acceptance of the programme and their desire to interact with their peers through social media. Suggestions to improve the platform included accessible chat histories, using more popular platforms such as Facebook or WhatsApp, and to have topical discussions where pertinent information for youth is provided.